Study of heat transfer on physiological driven movement with CNT nanofluids and variable viscosity. (November 2016) - Akbar, Noreen Sher; Kazmi, Naeem; Tripathi, Dharmendra; Mir, Nazir Ahmed
Highlights: CNT nanofluids driven by cilia induced movement is discussed. The problem is formulated in the form of nonlinear partial differential equations. Problem is simplified by using the dimensional analysis. Lubrication theory is employed to linearize the governing equations. Analytical solutions are obtained. Abstract: Background and objectives: With ongoing interest in CNT nanofluids and materials in biotechnology, energy and environment, microelectronics, composite materials etc., the current investigation is carried out to analyze the effects of variable viscosity and thermal conductivity of CNT nanofluids flow driven by cilia induced movement through a circular cylindrical tube. Metachronal wave is generated by the beating of cilia and mathematically modeled as elliptical wave propagation by Blake (1971). Methods, results and conclusions: The problem is formulated in the form of nonlinear partial differential equations, which are simplified by using the dimensional analysis to avoid the complicacy of dimensional homogeneity. Lubrication theory is employed to linearize the governing equations and it is also physically appropriate for cilia movement. Analytical solutions for velocity, temperature and pressure gradient and stream function are obtained. The analytical results are numerically simulated by using the Mathematica Software and plotted the graphs for velocity profile, temperature profile, pressure gradient and stream lines for better discussion and visualization. This model is applicable in physiological transport phenomena to explore the nanotechnology in engineering the artificial cilia and ciliated tube/pipe.